A functional magnetic resonance imaging study of cognitive control and neurosensory deficits in mild traumatic brain injury. Issue 11 (19th August 2015) - Mayer, Andrew R.; Hanlon, Faith M.; Dodd, Andrew B.; Ling, Josef M.; Klimaj, Stefan D.; Meier, Timothy B.
Abstract Mild traumatic brain injury patients (mTBI) frequently report symptoms of increased distractability and sensory disturbances during mutisensory stimulation. These common post‐concussive symptoms could putatively result from dysfunction within the cognitive control network (CCN; top‐down) or from unisensory cortex (bottom‐up) itself. Functional magnetic resonance imaging (fMRI) and high‐resolution structural data were therefore prospectively collected during a multisensory (audio‐visual) cognitive control task from 46 mTBI patients within 3 weeks of injury and 46 matched healthy controls (HC), with a subset of participants returning at 4 months. Multisensory stimuli were presented at two frequencies to manipulate cognitive and perceptual load. Patients self‐reported more cognitive, emotional, somatic, vestibular and visual symptoms relative to HC, which improved, but did not entirely resolve, over the 4 month follow‐up period. There were no group differences in behavior or functional activation during cognitive control (incongruent – congruent trials). In contrast, patients exhibited abnormal activation within different regions of visual cortex that depended on whether attention was focused on auditory or visual information streams. Patients also exhibited increased activation within bilateral inferior parietal lobules during higher cognitive/perceptual loads, suggesting a compensatory mechanism to achieve similar levels of behavioral performance. Functional abnormalities within the visual cortex and inferior parietal lobules were only partially resolved at 4 months post‐injury, suggesting that neural abnormalities may take longer to resolve than behavioral measures used in most clinical settings. In summary, current results indicate that abnormalities within unisensory cortex (particularly visual areas) following mTBI, which likely contribute to deficits commonly reported during multisensory stimulation. Hum Brain Mapp 36:4394–4406, 2015. © 2015 Wiley Periodicals, Inc.